The Influence Of Servicescape On Customer Satisfaction Coffee Shop Karya Karsa, Bandung - Luthfiani, Lulu Hasna; Tjahjawati, Sri Surjani (Jurnal Scientia, 2024)
Most Indonesians have changed their lifestyle by following the work from café (WFC) trend. This trend makes business people in the field of coffee shops must pay attention to a good servicescape to support customer satisfaction while on the move there. The purpose of this study was to determine the effect of servicescape on customer satisfaction of Karya Karsa Bandung Coffee. This research uses a quantitative approach method by sampling 120 respondents of Generation Z customers of Karya Karsa Bandung Coffee who do work from café (WFC) there. The results of the data collection were then processed with SPSS version 25. The result of this study is that servicescape has a positive and significant effect of 70.1% on customer satisfaction.